Mitochondrial Function and Energy Metabolism: Physiological Insights - Kurniawan, Muhammad Ahdi; Khairullah, Aswin Rafif; Pratama, Bima Putra; Hermadi, Herry Agoes; Wardhani, Bantari Wisynu Kusuma; Ansori, Arif Nur Muhammad; Ahmad, Riza Zainuddin; Kurniasih, Dea Anita Ariani; Rehman, Saifur; Mustofa, Imam; Utari, Fadhila; Yulianti, Wita; et al. (Trends in Sciences, 2025)
Mitochondria are vital organelles that function as the primary hub of cellular energy metabolism, integrating glycolysis, the Krebs cycle, and oxidative phosphorylation to sustain adenosine triphosphate (ATP) production. Beyond energy generation, mitochondria act as dynamic regulators of cellular homeostasis through processes such as fusion, fission, biogenesis, and mitophagy, as well as through redox and oxidative stress signaling. These mechanisms enable cells to adapt to fluctuations in nutrient availability, oxygen concentration, and energy demand, thereby maintaining metabolic flexibility and functional integrity across tissues, including muscle, liver, and brain. Mitochondrial dysfunction disrupts oxidative phosphorylation, promotes reactive oxygen species (ROS) accumulation, and reduces respiratory capacity, leading to metabolic, cardiovascular, and neurodegenerative disorders. Recent advances have revealed the critical regulatory roles of AMP-activated protein kinase (AMPK), mechanistic target of rapamycin (mTOR), and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) in controlling mitochondrial biogenesis, respiration, and stress responses. Additionally, the interactions between mitochondria and other cellular organelles are essential for maintaining energy balance and adapting to cellular stress. Technological innovations, including metabolomics, proteomics, and super-resolution microscopy, have enhanced our ability to study mitochondrial function at the molecular and tissue levels with unprecedented precision. Future research focusing on mitochondrial adaptation mechanisms and inter-organelle communication will provide a foundation for developing mitochondria-targeted therapeutic strategies aimed at improving energy efficiency, strengthening cellular resilience, and preventing degenerative disease progression. HIGHLIGHTS Mitochondria integrate energy production with redox and stress signalling. AMPK–mTOR–PGC-1α triad coordinates biogenesis, dynamics, and fuel selection. Tissue context matters: skeletal muscle, liver, and brain show distinct programs. Exercise and dietary cues rewire mitochondrial capacity and efficiency. Mitochondrial dysfunction links to T2D, obesity, and cardiometabolic disease—and points to targeted therapies. GRAPHICAL ABSTRACT